Your finances in changing times - Burkett, Larry (Campus Crusade for Christ, Inc., 1975)
With more than a million copies in print, this book is a perfect introduction to basic financial management. It is a complete money guide, offering practical suggestions for building a sound financial program. Following Burkett's time-tested, biblically grounded advice, you will learn to plan for a secure future, get out or stay out of debt, and enjoy the freedom that comes from having your financial house in order.